La Técnica y su Entrenamiento - Seirul-lo Vargas, F. (Apunts Medicina de l'Esport, 1987)
Technique is a concept with varied applications and a great diversity of contents. In contrast with other human technical activities, in sport activities all human capacities are involved and evaluated immediately. For this reason, there is a need for a more specific approach to the concept of technique. Ozolín, N. (1970) defines technique as the most rational and effective form to perform exercises. Grosser, M. (1982) defines technique as the ideal model of a movement relative to a specific sport activity. For team sports; Mechling (1983) defines technique as that movements or part of movements that permit to perform attack and defense actions with a concrete game purpose, and with a quite good execution quality (good with reference to an ideal model). It follows from these definitions that the sportsman, in order to obtain performance in his particular sport, must have learned a group of movements, following ideal models, result of different research, which will facilitate to execute precise actions to improve his motor skills. Therefore, when a person possess this or that movement within his motor repertory, it is said that he has this or that ability; that is why, the group of movements of different sport specialties are called sport technical abilities. Harre, D.(1979), Grosser, M. (1982), Roth (1983). Consequently, an sportsman will possess a good technical ability the best he adjust his movement to the ideal model, in addition to the best he can control it to obtain maximal performance during real competition. The aptitude of a person to acquire these abilities is understood as capacity (Thiess, 1980). Thus, an individual with a better learning capacity, will have the possibility to have a major number of technical abilities to apply to sport executions (Hortz, 1983). We should point out, in passing, that to apply correctly a technical ability during competition not only depends of this capacity, but also on tactical capacities which are not the motive of this article.